Therapeutic management of hyperprolactinemia: a literature review (Research, Society and Development, 2021)
Introduction: Prolactin (PRL) is a hormone synthesized and secreted by the lactotrophic cells of the anterior pituitary, whose main function is to stimulate lactation. Hyperprolactinemia is defined as excess production of prolactin and is the most common pituitary hormonal disorder found in medical practice. Methodology: It consists of a literature review, with a qualitative and integrative approach, on the therapeutic management of hyperprolactinemia. Scientific texts were selected from the Scientific Electronic Library Online (SciELO) and from the U.S. National Library of Medicine (PubMED), using the descriptors “hyperprolactinemia” and “treatment”. Results and discussion: The therapeutic management of hyperprolactinemia depends on establishing its etiology, which can be pathological, including prolactinomas and primary hypothyroidism; pharmacological, with the use of antipsychotics; or physiological, due to chest wall injuries, stress or breastfeeding. In general, treatment is aimed at preserving or restoring gonadal function and preventing side effects of increased PRL levels, such as osteoporosis. Conclusion: With the review of the scientific literature, it is clear that the investigation of the etiology of hyperprolactinemia is essential for the therapeutic decision. The classic approach, performed with AD, especially CAB, is still considered the first line for the treatment of prolactinomas, regardless of size. Other drug options include HRT, such as Tamoxifen and Clomiphene, which have been shown to be beneficial options for invasive and resistant macroprolactinomas; and restoration of eugonadism, respectively.